Implementation of Sharia Principles in the Drafting of Financing Agreements in Islamic Financial Institutions: Implementasi Prinsip Syariah dalam Penyusunan Perjanjian Pembiayaan di Lembaga Keuangan Syariah - Mursekha, Mursekha; Wahyuningsih, Avita Mutiara Tri; Istiqomah, Diah; Rizqi, Salsa Khasbiana (Journal of Society and Development, 2024)
Islamic financial institutions are obligated to ensure that every operational activity aligns with Sharia principles. One of the most crucial aspects in this regard is the formulation of financing contracts. These contracts are not merely formal legal documents but also reflect a moral commitment between the institution and the customer, which must be free from elements prohibited in Islam, such as Riba (interest), Gharar (uncertainty), and Maysir (speculation). This study aims to explore the extent to which Sharia principles have been implemented in the drafting of financing contracts, as well as to examine the challenges faced by Islamic financial institutions in the process. A descriptive qualitative method was employed, utilizing literature review and in-depth interviews with practitioners in the Islamic banking sector. The findings reveal that although Islamic financial institutions have administratively incorporated Sharia principles into financing agreements, there are discrepancies in interpretation and implementation at the practical level. Contributing factors include limited human resources with adequate knowledge of Fiqh Muamalah, inconsistencies between internal regulations and fatwas issued by the National Sharia Council (DSN-MUI), and market pressures demanding operational efficiency. This research contributes by identifying the gap between regulation and practice and provides recommendations for improving human resource training and harmonizing internal policies. The findings are expected to serve as input for regulators, academics, and practitioners in strengthening Sharia governance within the financial sector.